Tinjauan Hukum Islam Terhadap Praktek Jual Beli Pupuk Kandang(Studi Kasus Di Dusun Sodong Desa Tengklik Kec. Tawangmangu Kab. Karanganyar Jawa Tengah) - Wicaksono, Aqsathu; , Dr. Muhammad Muhtarom, SH. MH (2017)
In Sodong Tengklik, there is practically buying and selling manure that its basic ingredients are made from animal waste. Based on such description, researcher interested in studying and analyzing how the tradition of the practice of buying and selling real manure according to the contract agreement in mu'amalah (shari'a contract) and the Islamic law in force. The purpose of this research is to review the Islamic law against the practice of buying and selling manure in Sodong Tengklik, Tawangmangu, Karanganyar Central Java. This research is a field research with qualitative approach. The methods used in data collection are interview and documentation, while in data analysis is the inductive method. The practice of buying and selling manure in Sodong Tengklik, Tawangmangu, Karanganyar Central Java has been in accordance with the terms of buying and selling in harmony and although the base material of manufacture of manure is manure in accordance with his nature as a thing disgusting and bad, followed by its nature that is dirty, smelly and disgusting. But first there is the opinion that explains that livestock manure is not odious because it comes from animal waste edible flesh. The second opinion is the theological opinion which allows to take advantage of an object and peddle copies the records do not violate Islamic law.